mHealth Series: Text messaging data collection of infant and young child feeding practice in rural China - A feasibility study - Xiaozhen Du; Wei Wang; Michelle Helena van Velthoven; Li Chen; Robert W. Scherpbier; Yanfeng Zhang; Qiong Wu; Ye Li; Xiuqin Rao; Josip Car (Edinburgh University Global Health Society, 2013)
Face-to-face interviews by trained field workers are commonly used in household surveys. However, this data collection method is labor-intensive, time-consuming, expensive, prone to interviewer and recall bias and not easily scalable to increase sample representativeness. The study explored the feasibility of using text messaging to collect information on infant and young child feeding practice in rural China.